"Get-Rich-Quick Rituals, Remote Sex, and Herbs in Vaginal Canals": Portrayal of Indigenous Fruits and Medicinal Herbs in Zimbabwe's The Mirror Newspaper. Issue 4 (2nd October 2022) - Moyo, Oswell; Ureke, Oswelled
Abstract: This article examines how The Mirror, a regional newspaper in Zimbabwe, represents issues related to indigenous knowledge, such as the use of medicinal herbs and fruits. The Mirror largely circulates in the Midlands and the Masvingo region, although it also has a presence in parts of Mashonaland East, Manicaland, and Matabeleland South. The article utilises a qualitative methodology, in which archival data were collected from The Mirror to examine its portrayal of indigenous fruits and medicinal herbs. As such, representation theory is the theoretical lens of the study, and the data are analysed using thematic analysis. The study found that stories related to indigenous fruits and medicinal herbs are narrated through an urban gaze, which is sometimes at odds with the common uses of such resources by rural communities. It is argued in this article that The Mirror, as a post-colonial media entity, does not deviate from the colonial practices of suppressing and attacking African culture. Indigenous herbs are framed in terms such as witchcraft, bizarre incidents, and lack of efficacy. Furthermore, news stories published by The Mirror do not provide complete information on the uses of indigenous fruits and medicinal herbs, but instead focus only on what journalists perceive as "newsworthy" and appropriate for their readers.